Modeling and Simulation of Nine-Level Cascaded H-Bridge Multilevel Inverter - A.A. Zulkefle; A.I.A. Rahman; M. Zainon; Z.A. Baharudin; Z. Zakaria; M.B. Farriz; S.A.A. Shukor; N.F. Johan; N. Saleh; M.A.M. Hanafiah (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper analyzed a single phase nine level cascaded h-bridge multilevel inverter (CHMLI) topology in which requires lesser number of components and easier to control if compared to other methods. The inverter of different voltage levels (up to 9-Levels) are designed and simulated using MATLAB Simulink. A Level Shifted Multi-Carrier PWM control scheme is used to control the operation of the power switches for CHMLI topology. The results are compared in terms of THD.  The value of THD is found to be reduced as the number of voltage level of CHMLI is increased.